Importance of Diversity in the Oral Microbiota including Candida Species Revealed by High-Throughput Technologies - Tamaki Cho; Jun-ichi Nagao; Rieko Imayoshi; Yoshihiko Tanaka (Hindawi Limited, 2014)
Taking advantage of high-throughput technologies, deep sequencing of the human microbiome has revealed commensal bacteria independent of the ability to culture them. The composition of the commensal microbiome is dependent on bacterial diversity and the state of the host regulated by the immune system. Candida species are well known as components of the commensal oral microbiota. Candida species frequently colonize and develop biofilms on medical devices like dentures and catheters. Therefore, Candida biofilm on dentures leads to a decrease in the bacterial diversity and then to a change in the composition of the oral microbiota. A disturbance in the balance between commensal bacteria and the host immune system results in a switch from a healthy state to a diseased state even in the limited oral niche.